2016
DOI: 10.1007/s11606-016-3651-0
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Cost-Effectiveness of 13-valent Pneumococcal Conjugate Vaccine for Adults Age 50 Years and Older in the United States

Abstract: BACKGROUND:Recently released results from a randomized controlled trial have shown that 13-valent pneumococcal conjugate vaccine (PCV13) is efficacious against vaccine-type nonbacteremic pneumonia in adults. OBJECTIVE: We examined the incremental costeffectiveness of adding PCV13 to the Advisory Committee on Immunization Practices (ACIP) adult immunization schedule. METHODS:We used a probabilistic model following cohorts of 50-, 60-, or 65-year-olds. We used separate vaccination coverage and disease incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 23 publications
2
62
1
Order By: Relevance
“…This study shows a reduction in pneumococcal disease when adding PCV13 to the regimen, similar to another analysis comparing current recommendations with PCV13 recommendation for high risk patients; however cost outcomes are not comparable because that study did not examine a strategy of vaccinating everyone aged 50-64, regardless of comorbidity status. 23 A CE analysis evaluating PCV13 vaccination in healthy adults with no high risk conditions over 50 years in Belgium compared to PPSV23 vaccination and both vaccines combined resulted in a higher ICER for PCV13 than that seen in our study. When comparing PCV13 with PPSV23, the cost and effectiveness of each were similar, with the higher price of PCV13 being the driving factor in a higher ICER for PCV13.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…This study shows a reduction in pneumococcal disease when adding PCV13 to the regimen, similar to another analysis comparing current recommendations with PCV13 recommendation for high risk patients; however cost outcomes are not comparable because that study did not examine a strategy of vaccinating everyone aged 50-64, regardless of comorbidity status. 23 A CE analysis evaluating PCV13 vaccination in healthy adults with no high risk conditions over 50 years in Belgium compared to PPSV23 vaccination and both vaccines combined resulted in a higher ICER for PCV13 than that seen in our study. When comparing PCV13 with PPSV23, the cost and effectiveness of each were similar, with the higher price of PCV13 being the driving factor in a higher ICER for PCV13.…”
Section: Discussioncontrasting
confidence: 48%
“…As part of the sensitivity analysis, we focused on a secondary baseline value of 24.5% for PCV13 pneumococcal illness serotype coverage likelihood, based on updated CDC serotype likelihood data (2015-2016, unpublished data), slightly lower than values in a recent CDC analysis (24.8-26.75%). 23 Death due to non-pneumococcal causes was modeled using U.S. mortality data. 45 In the base case analysis, equal nonpneumococcal mortality risk was assumed in average-and high-risk health states, thus making model assumptions more favorable toward strategies where only high-risk patients are vaccinated; this assumption was tested in sensitivity analyses, where the effects of higher mortality in highrisk patients were examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent review by Treskova et al (2019) 18 stratifies the newer literature according to assumptions about herd effects from pediatric vaccination (i.e., whether effects were ongoing or completed, whether effects were from pediatric PCV13 (PCV13 Pediatric) or from pediatric 10-valent pneumococcal conjugate vaccine (PCV10 Pediatric), or whether there was a switch in pediatric vaccination from PCV10 to PCV13 or vice versa), and according to the policy being evaluated (PPV23 versus no vaccination, PCV13 versus no vaccination, and adding PCV13 to PPV23). Of the four studies that evaluate the addition of PCV13 Adult to adult PPV23 (as was the case in Turkey), van Hoek and Miller (2016), 20 Blommaert et al (2016), 21 and Willem et al (2018) 22 found doing so to be cost-ineffective, while Stoecker et al (2016) 23 found it to be cost-effective only in the short run before herd effects fully set in. Treskova et al (2019) 18 conclude from this evidence that PCV13 Adult is not cost-effective in the presence of herd effects from PCV13 Pediatric.…”
Section: Literature On Economic Evaluation Of Pcv13 Adultmentioning
confidence: 99%
“…In our model we projected these rates forward to account for the indirect protection provided by additional serotypes in PCV13 not covered by the 7-valent version [9][10][11][12].…”
Section: Disease Parametersmentioning
confidence: 99%